OPTIMASI KOMBINASI ALAT BERAT PADA PROYEK PEMBANGUNAN GEDUNG RSUD SANJIWANI GIANYAR - I Ketut Ariadi; Anak Agung Gde Agung Yana; A. A. Diah Parami Dewi (JURNAL SPEKTRAN, 2021)
Construction equipment, especially heavy equipment, is one of the important resources in the implementation of construction projects. Heavy equipment can streamline the number of workers and the completion of projects can be faster. The selection of heavy equipment must be in accordance with the work during construction, and the efficiency of the equipment must be considered. The construction project of the Sanjiwani Hospital, Gianyar Regency is a construction project that requires heavy equipment, so this project needs management in terms of time and cost efficiency of using heavy equipment. The purpose of this study was to analyze the most optimum combination of heavy equipment in terms of time and cost in excavation and soil embankment work, so that losses due to project delays can be avoided. The method used in this research is the calculation of production capacity and cost efficiency on each heavy equipment. The results of the analysis show that the effective combination of heavy equipment for excavation work is 9,153.89 m3 and embankment is 456.80 m3, namely a combination of 2 Komatsu PC200-8 Excavator, 3 Komatsu WA200-1 Wheel Loaders, and 11 Hino Dutro Dump Trucks capacity 9 m3. The work can be completed in 185 hours at a total cost of IDR 162,363,500.00. The use of this combination can speed up the time by 95 hours (33.93%) and can save costs of IDR 47,468,500.00 (22.62%) of the existing condition.